Copper hexacyanoferrate functionalized single-walled carbon nanotubes for selective cesium extraction. (6th July 2017) - Draouil, H.; Alvarez, L.; Causse, J.; Flaud, V.; Zaibi, M. A.; Bantignies, J. L.; Oueslati, M.; Cambedouzou, J.
Abstract : Single-walled carbon nanotubes (SWCNTs) are functionalized with copper hexacyanoferrate (CuHCF) nanoparticles to prepare solid substrates for sorption of cesium ions (Cs + ) from liquid outflows. Abstract : Single-walled carbon nanotubes (SWCNTs) are functionalized with copper hexacyanoferrate (CuHCF) nanoparticles to prepare solid substrates for sorption of cesium ions (Cs + ) from liquid outflows. The high mechanical resistance and large electrical conductivity of SWCNTs are associated with the ability of CuHCF nanoparticles to selectively complex Cs + ions in order to achieve membrane-like buckypapers presenting high loading capacity of cesium. The materials are thoroughly characterized using electron microscopy, Raman scattering, X-ray photoelectron spectroscopy and thermogravimetric analyses. Cs sorption isotherms are plotted after having measured the Cs + concentration by liquid phase ionic chromatography in the solution before and after exposure to the materials. It is found that the total sorption capacity of the material reaches 230 mg g −1, and that about one third of the sorbed Cs (80 mg g −1 ) is selectively complexed in the CuHCF nanoparticles grafted on SWCNTs. The quantification of Cs + ions on different sorption sites is made for the first time, and the high sorption rates open interesting outlooks in the integration of such materials in devices for the controlled sorption and desorption of these ions.